Effect of the physical rehabilitation program based on self-care ability in patients with acute ischemic stroke: a quasi-experimental study - Li, Ying; Wang, Qian; Liu, Xiao-Ling; Hui, Rong; Zhang, Yin-Ping (Frontiers in Neurology, 2023)
Introduction It is the most practical goal of limb rehabilitation for stroke patients to make the upper limb, trunk, and lower limb joints link together as a whole and restore the ability to self-care. However, many previous studies focused on the single joint or single muscle group movement of stroke patients and did not integrate self-care ability training into the whole process of rehabilitation, which lacks accuracy, integrity, and systematization. Methods A quasi-experimental study was conducted in a tertiary hospital. Eligible patients were recruited according to the inclusion criteria and exclusion criteria and then divided into an experimental group (n = 80) and a control group (n = 80) by the medical district. The control group received the routine physical rehabilitation intervention. The experimental group adopted the physical rehabilitation program based on self-care ability led by the nurses specializing in stroke rehabilitation to carry out the multi-joint coordinated exercise based on the control group. The training time and frequency were the same in both groups (45 min per session, one session per day for three consecutive months). The primary outcome was myodynamia. Secondary outcomes were the modified Barthel Index (MBI) and Stroke Specific Quality of Life Scale (SS-QOL). The primary and secondary outcomes were assessed before the intervention and at 1 and 3 months of intervention. In this study, the TREND checklist was followed for non-randomized controlled trials. Results A total of 160 participants completed the study. The physical rehabilitation program based on self-care ability was better than the routine rehabilitation program. With the prolongation of intervention time, all outcomes improved gradually in the experimental group (P < 0.05), and the myodynamia of lower limbs recovered faster than that of upper limbs. In the control group, the myodynamia of the affected limb was not significantly improved (P > 0.05), with only a small increase in MBI and SS-QOL scores (P < 0.05). Conclusion The physical rehabilitation program based on self-care ability after stroke was beneficial for acute ischemic stroke patients and improved the patient's myodynamia, quality of life, and self-care ability within the third month.